SELECTED FACTORS CONTRIBUTING TO ALCOHOLISM AMONG SECONDARY SCHOOL STUDENTS IN MWIMBI DIVISION, KENYA - Munyua, Millicent Makena; Nyaga, Veronica Karimi; Oundo, Monicah Buyatsi (European Scientific Journal, ESJ, 2014)
Alcoholism has devastating effects especially on students’ academic achievement and future career prospects. Therefore, this study sought to determine the factors contributing to the high rate of alcohol consumption among secondary school students in Mwimbi Division, Kenya. The study employed the descriptive survey research design on a sample size of 320 Form three students from secondary schools within Mwimbi division. Questionnaires were utilized as research instruments for collecting the necessary data while data analysis was carried out using SPSS version 14.0. The study findings indicated that pertinent factors including stress, alcoholic background, lack of religious morals, excess pocket money, broken families, low price of alcohol, availability of alcohol, peer influence and unpleasant school condition contributed to alcoholism among secondary school students. Hence, to mitigate alcoholism among students, it was recommended that school conditions be improved, parents desist from providing excessive pocket money to students, the government to regulate the sale of alcohol and religious institutions to make efforts in instilling religious values among the students.